Utilizing Pineapple Pomace in Snack Noodle Production: Quality Assessment and Textural Analysis - Abdul Razak, Siti Nurul Aina; Kormin, Faridah (Enhanced Knowledge in Sciences and Technology, 2025)
Snack noodles are used because they are quick to prepare, novel in texture and taste, and therefore suitable for the snacking industry. Pineapple pomace-based snack noodles were the focus of this research in a bid to enhance their nutritional and sustainability content. Commercial snack noodles were compared with 10%, 20%, 30%, and 40% pineapple pomace powder formulations on the basis of quality, texture, and acceptability to the consumer. This evaluation included major parameters of moisture, texture, and colour, quantified in terms of L*, a*, and b* values. Results showed sample difference with statistical significance (p